An indigenous inland genotype of the black yeast Hortaea werneckii inhabiting the great pyramid of Giza, Egypt - Rizk, Samah Mohamed; Magdy, Mahmoud (Frontiers in Microbiology, 2022)
Abstract: Within the context of cultural heritage conservation, the biological study of tangible archeological sites is an important task to extend their existence and strengthen the transmission of their cultural value to future generations. In Egypt, a hyper-arid region, a microcolonial fungus with inky black growth was observed on a stone surface in the royal corridor of the Great Pyramid of Giza (King Khufu’s pyramid). The isolate was studied and characterized by microscopic morphometric measurements, evaluation of enzymatic activities, and genotyping techniques. The isolate was identified as Hortaea werneckii, a pleomorphic black yeast that naturally inhabits hypersaline environments and infects human skin. It has been reported from humid temperate, subtropical, and tropical zones, mainly from marine habitats and adjacent areas, and is associated with marine life. Since it was observed in an unusual habitat, it raises the question about its type and origin, whether environmental or clinical. The Egyptian isolate Hortaea werneckii GPS5 was profiled and characterized by adaptive extremophilic tolerance to arid and salt stress, low portability to infect human skin, the capability of solubilizing calcite and phylogenetically clustered with previous recorded environmental accessions. A profile that matches the biodeterioration fungal agents known as rock-inhabiting fungi, a potential threat to cultural heritage sites that requires attention and prevention plans.